Infrared spectra of adsorbed ethene on the EUROPT-1 catalyst - McDougall, Gordon; De La Cruz, Carlos; Chesters, Michael; Sheppard, Norman (Ciencia)
The infrared spectra from the adsorption of ethene on the EUROPT- 1 catalyst, at room temperature, indicate a complex surface hydrocarbon-phase consisting of four species. Three are identified as ethylidyne, ï°-ethene and di-ï³ adsorbed ethene. The most likely identity of the fourth is a C4 species derived from the dimerisation of the other adsorbed C2 hydrocarbons.